2017
DOI: 10.1002/anie.201706071
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria‐Assisted Activation of Antimicrobial Polypeptides by a Random‐Coil to Helix Transition

Abstract: The application of antimicrobial peptides (AMPs) is largely hindered by their non-specific toxicity against mammalian cells, which is usually associated with helical structure, hydrophobicity, and charge density. A random coil-to-helix transition mechanism has now been introduced into the design of AMPs, minimizing the toxicity against mammalian cells while maintaining high antimicrobial activity. By incorporating anionic phosphorylated tyrosine into the cationic polypeptide, the helical structure of AMPs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 45 publications
1
81
0
1
Order By: Relevance
“…The above results suggested that endogenous ALP selectively triggered the conversion of ALP PS into PS Se‐I with an “off‐on” activation of the photosensitized 1 O 2 generation, and thus induced cell death upon light irradiation within the therapeutic window. Since ALP is known to be overproduced in many types of cancer cells and bacteria, ALP PS could be used as a promising activatable photosensitizer for specific ablation of tumor and bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggested that endogenous ALP selectively triggered the conversion of ALP PS into PS Se‐I with an “off‐on” activation of the photosensitized 1 O 2 generation, and thus induced cell death upon light irradiation within the therapeutic window. Since ALP is known to be overproduced in many types of cancer cells and bacteria, ALP PS could be used as a promising activatable photosensitizer for specific ablation of tumor and bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The conventional α‐helical AMPs may lead to adverse peptide interactions with plasma proteins and suffer from a fast clearance from the bloodstream . To balance the bioaccessibility and bactericidal efficacy, Cheng and Xiong et al developed a series of secondary structure transitionable polypeptides for infection control . A class of pH‐sensitive, helix–coil conformation transitionable antimicrobial polypeptides (HCT‐AMPs) were developed, which bear randomly presented anionic carboxyl groups and cationic poly(γ‐6‐ N ‐(methyldihexylammonium)hexyl‐ l ‐glutamate) (PHLG‐MHH) residues.…”
Section: Antimicrobial Systemsmentioning
confidence: 99%
“…For example, the poly(g‐6‐( N , N ‐dimethyl‐ N ‐octylamino)hexyl‐ l ‐glutamate)‐r‐(poly‐ l ‐tyrosine) (PHOT) was modified via phosphorylation of the phenol residues of tyrosine, changing its secondary structure from helical to random coil. The bacterial phosphatases secreted from Bacillus cereus or S. aureus can efficiently hydrolyze the phosphates, subsequently returning structures of polypeptides back to helical with an enhanced bactericidal efficacy (Figure B) . Taken together, the adaptive secondary structure transitional polypeptides provided an efficient alternative path way to balance the toxicity and the bactericidal activity of a polymer and possess great potential in clinical transition.…”
Section: Antimicrobial Systemsmentioning
confidence: 99%
See 2 more Smart Citations